The Phenotypic Consequences of CFTR Mutations - Rowntree, Rebecca K.; Harris, Ann (Annals of human genetics, 2003)
Summary Cystic fibrosis is a common autosomal recessive disorder that primarily affects the epithelial cells in the intestine, respiratory system, pancreas, gall bladder and sweat glands. Over one thousand mutations have currently been identified in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene that are associated with CF disease. There have been many studies on the correlation of the CFTR genotype and CF disease phenotype; however, this relationship is still not well understood. A connection between CFTR genotype and disease manifested in the pancreas has been well described, but pulmonary disease appears to be highly variable even between individuals with the same genotype. This review describes the current classification of CFTR mutation classes and resulting CF disease phenotypes. Complex disease alleles and modifier genes are discussed along with alternative disorders, such as disseminated bronchiectasis and pancreatitis, which are also thought to result from CFTR mutations.